Review of the world genera of Phanacidini (Hymenoptera: Cynipoidea: Cynipidae), with the first record from China and a new tribal diagnostic character - Nastasi, Louis F.; Deans, Andrew R. (Zootaxa, 2025)
We review the genera of Phanacidini and provide updated diagnoses for each genus and a new key to the four genera. We also redescribe the enigmatic herb gall wasp Diakontschukia saussureae Diakontschuk, 2001 (Hymenoptera: Cynipidae: Phanacidini), based on a specimen collected in Haopingsi Nature Reserve, China. This is the first record of the tribe Phanacidini in China. Lastly, we provide extensive commentary on the validity of diagnostic characters that have been used for Phanacidini relative to other herb gall wasp tribes. We carried out a survey of Aulacideini, Aylacini, and Phanacidini to identify whether the length of F1 relative to F2 was of diagnostic value at the tribal level, finding that F1 was always conspicuously longer than F2 in Phanacidini and Aylacini but at most subequal to F2 in Aulacideini, suggesting that this is indeed a valuable character for diagnosing herb gall wasp tribes. Other characters discussed are the closure of the marginal cell and the dimensions of the mesopectus.